2023
DOI: 10.3389/fendo.2023.985404
|View full text |Cite
|
Sign up to set email alerts
|

The effects of three different low-volume aerobic training protocols on cardiometabolic parameters of type 2 diabetes patients: A randomized clinical trial

Abstract: ObjectiveTo compare the effects of different aerobic training protocols on cardiometabolic variables in patients with type 2 diabetes mellitus (T2DM).MethodsThis study was a parallel clinical trial. Fifty-two men and women with T2DM (>40 years) were randomly allocated into three groups, and 44 (22 males/22 females) were included in the final analysis. Exercise intensity was based on the speed corresponding to the maximum oxygen consumption (vV˙O2max). Moderate intensity continuous training (MICT) involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
3
0
1
Order By: Relevance
“…Exercise training has been shown to be an effective tool for health promotion [9][10][11][12][13][14] , can reduce the risk of cardiovascular disease and improve cardiac function and structure in patients with T2DM [15][16][17][18] . However, there are limited data on the effects of exercise on cardiac function and structure in patients with asymptomatic T2DM, and the effects of the type and mode of exercise intervention on cardiac function and structure are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training has been shown to be an effective tool for health promotion [9][10][11][12][13][14] , can reduce the risk of cardiovascular disease and improve cardiac function and structure in patients with T2DM [15][16][17][18] . However, there are limited data on the effects of exercise on cardiac function and structure in patients with asymptomatic T2DM, and the effects of the type and mode of exercise intervention on cardiac function and structure are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Any form of regular physical activity can benefit the patient (17). Glycosylated hemoglobin and fasting glucose levels significantly decreased in patients with diabetes who participated and improved their performance in aerobic, resistance, and combined exercises (18).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, HIE for even short durations of <10 min (e.g., six bouts of 1 min high-intensity incline walking) could decrease postprandial BG levels and 24 h BG levels [3][4][5][6]. Furthermore, a recent randomized controlled trial showed the chronic effect of short-duration HIE on glycated hemoglobin (HbA1c) in individuals with T2D [7]. An eight-week HIE program (five bouts of two minutes of walking/running on a treadmill at 100% of VO 2 max with an interval of two minutes) significantly improved HbA1c levels (mean value: −1.80%).…”
Section: Introductionmentioning
confidence: 99%